STATE OF VACCINEPROPHYLAXIS OF POLIOMYELITIS IN UKRAINE - А. Ю. Фесенко; В. К. Позур; В. I. Бондаренко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
Аi m. To determine the level of protective antibodies in children and to analyze the level of vaccination coverage of children in regions of Ukraine. Methods. It was used serological, statistical and epidemiological methods and cell culture Hep-2. Results. It was determined the levels of protective antibodies to 1, 2, 3 types of poliovirus vaccine strains of 40 people aged 15–17 years using the microneutralization method. According to data provided by the regional sanitary-epidemiological stations of Ukraine, it was conducted a retrospective analysis of vaccination status against polio in 2009–2012 in accordance with the calendar of vaccination in Ukraine. The retrospective analysis of the data showed a low level of vaccination in 2012, when vaccination coverage of children under 1 year was 45.9%. Revaccination at 18 months this year held only 41.7% of persons, in 6 years 53.9% of children received oral polio vaccine, 56.9% of children was vaccinated in 14 years. The research found that 5% of children had protective antibodies against the poliovirus types 1 and 2, 10% of surveyed individuals were unprotected against poliovirus type 3. Indicators titers of antibodies to type 3 polioviruses were lower than those of polio virus types 1 and 2.